High frequency and microwave engineering - Silva, Ed da. (Oxford ; Boston : Butterworth-Heinemann, 2001)
With the increased use of mobile phones and computer wireless techniques, a need has developed for a book which provides students and industry with expertise in radio and microwave engineering. This important text has been written with these aims in mind. *Provides a comprehensive course in radio and microwave engineering *Includes CD-ROM, containing the CAD package PUFF 2.1 for construction and evaluation of circuits; and a comprehensive section on practical aspects of design *Written by an experienced author, in a clear and easy-to-follow style *Contains a variety of examples and self-test questions with model answers The material covers transmission lines, scattering parameters, couplers, amplifiers, oscillators and phase-locked loops in a novel way by introducing examples from daily life prior to the introduction of the theory. Microwave tools such as Smith charts, scattering parameters and signal flow diagrams are dealt with thoroughly and are fully integrated in the numerous examples throughout the text and with PUFF. High Frequency and Microwave Engineering is intended as an advanced undergraduate text for students of electrical and communication engineering, and is also eminently suitable for self-study and as a manual for those in the industry wishing to update their engineering skills. Provides a comprehensive course in radio and microwave engineering Contains many examples and self-test questions with model answers.
Basic features of radio communication systems * Transmission lines * Smith Charts and scattering parameters * Puff software * Amplifier basics * High frequency transistor amplifiers * Microwave amplifiers * Oscillators and frequency synthesizers * Further topics * Book references.
Includes bibliographical references and index.
Includes CD-ROM in pocket attached to inside back cover.
CD-ROM contains CAD package PUFF 2.1 for construction and evaluation of circuits and a section on practical aspects of design.
Keywords: Microwave devices; Microwave circuits; Wireless communication systems; Microwave communication systems; Electronic books